Diverse Effects of Lead Nitrate on the Proliferation, Differentiation, and Gene Expression of Stem Cells Isolated from a Dental Origin. (10th December 2013) - Abdullah, Mariam; Rahman, Fazliny Abd.; Gnanasegaran, Nareshwaran; Govindasamy, Vijayendran; Abu Kasim, Noor Hayaty; Musa, Sabri
Abstract : Lead (Pb 2+ ) exposure continues to be a significant public health problem. Therefore, it is vital to have a continuous epidemiological dataset for a better understanding of Pb 2+ toxicity. In the present study, we have exposed stem cells isolated from deciduous and permanent teeth, periodontal ligament, and bone marrow to five different types of Pb 2+ concentrations (160, 80, 40, 20, and 10 µ M) for 24 hours to identify the adverse effects of Pb 2+ on the proliferation, differentiation, and gene expression on these cell lines. We found that Pb 2+ treatment altered the morphology and adhesion of the cells in a dose-dependent manner. There were no significant changes in terms of cell surface phenotypes. Cells exposed to Pb 2+ continued to differentiate into chondrogenesis and adipogenesis, and a severe downregulation was observed in osteogenesis. Gene expression studies revealed a constant expression of key markers associated with stemness (Oct 4, Rex 1) and DNA repair enzyme markers, but downregulation occurred with some ectoderm and endoderm markers, demonstrating an irregular and untimely differentiation trail. Our study revealed for the first time that Pb 2+ exposure not only affects the phenotypic characteristics but also induces significant alteration in the differentiation and gene expression in the cells.